Lo Stato laico costituzionale di diritto di fronte all’emergenza del terrorismo islamista (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Introduzione - 2. La lunga tradizione del diritto islamico - 2.1. La norma religiosa nelle impostazioni radicalizzanti - 3. La reazione dei legislatori e il ruolo dei giusdicenti. Brevi considerazioni sul caso degli USA - 3.1. Brevi considerazioni sul caso della Francia - 4. La reazione dei legislatori e il ruolo dei giusdicenti in Italia - 5. Conclusioni.ABSTRACT: What is the real relationship between the existing forms of (religious) terrorism and Islam? And how do the Western constitutional democracies react in times of emergency and threats of so-called Islamic terrorism? The article tries to answer these questions, focusing the attention on specific issues, such as those referring to the Islamic tradition - and the relative legal system - and some national legal orders, like the USA, France and Italy.